Multisector Nutrition Program Governance and Implementation in Ethiopia: Opportunities and Challenges. (December 2015) - Kennedy, Eileen; Tessema, Masresha; Hailu, Tesfaye; Zerfu, Dilnesaw; Belay, Adamu; Ayana, Girmay; Kuche, Desalegn; Moges, Tibebu; Assefa, Tsehai; Samuel, Aregash; Kassaye, Tarik; Fekadu, Habtamu; et al.
Governments globally are stressing both direct nutrition interventions combined with nutrition sensitive policies and programs to combat malnutrition. Governance at all levels has been identified as a critical element in ensuring success of national nutrition plans. For example, the most recent National Nutrition Program (NNP) in Ethiopia discusses the essentiality of governance and coordination at all levels. The research uses a qualitative study based on semi-structured interviews with key informant. The research discussed in this article focuses on governance structures from national to regional to district level in Ethiopia with an emphasis on translation of a strategy and implementation of the NNP. This article concentrates primarily on results from the national and regional levels. Data at both the national and regional levels indicate that there is general agreement on the nature of the nutrition problems in Ethiopia. At all levels of government, under nutrition, food insecurity, and micronutrient deficiencies were listed as the main nutrition problems. The challenges in governance and implementation identified at both the national and regional levels, however, varied. The implementation of the 2013 NNP was in its early stages at the time of this research. While there was palpable energy around the launch of the NNP, respondents indicated issues related to leadership, coordination, collaboration, advocacy, and budget would be challenges in sustaining momentum.